2006
DOI: 10.1523/jneurosci.5437-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Activation Drives Compartment-Selective Endocytosis and Axonal Targeting of Type 1 Cannabinoid Receptors

Abstract: The type 1 cannabinoid receptor (CB1R) is one of the most abundant G-protein-coupled receptors (GPCRs) in the brain, predominantly localized to axons of GABAergic neurons. Like several other neuronal GPCRs, CB1R displays significant in vitro constitutive activity (i.e., spontaneous activation in the absence of ligand). However, a clear biological role for constitutive GPCR activity is still lacking. This question was addressed by studying the consequences of constitutive activation on the intracellular traffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
213
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 186 publications
(231 citation statements)
references
References 45 publications
14
213
3
1
Order By: Relevance
“…This is in line with the data published by McDonald et al, which showed no alterations in the cellular distribution of CB 1 R upon inverse agonist treatment in neurons (McDonald et al, 2007a). In contrast, a previous study using inverse agonist treatment (Leterrier et al, 2006), and our study using DAGL-inhibitor treatment (Turu et al, 2007) have shown an inhibition of basal endocytosis of the receptor upon these treatments, suggesting a role for basal CB 1 R activity in this process. Since active receptors internalize by β-arr2-dependent mechanism, those results may seem to be contradictory with our present results, where we now find that interfering with β-arr2 expression or function does not have effect on constitutive endocytosis.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This is in line with the data published by McDonald et al, which showed no alterations in the cellular distribution of CB 1 R upon inverse agonist treatment in neurons (McDonald et al, 2007a). In contrast, a previous study using inverse agonist treatment (Leterrier et al, 2006), and our study using DAGL-inhibitor treatment (Turu et al, 2007) have shown an inhibition of basal endocytosis of the receptor upon these treatments, suggesting a role for basal CB 1 R activity in this process. Since active receptors internalize by β-arr2-dependent mechanism, those results may seem to be contradictory with our present results, where we now find that interfering with β-arr2 expression or function does not have effect on constitutive endocytosis.…”
Section: Discussionsupporting
confidence: 93%
“…However, in hippocampal neurons, it has been demonstrated that agonist treatment leads to internalization (Coutts et al, 2001). These data, together with differences detected in the regulation of constitutive internalization (Leterrier et al, 2006;McDonalds et al, 2007a) are in good agreement with our results…”
Section: Recent Work By Kleyer and Colleagues Demonstrated That In Imsupporting
confidence: 93%
See 3 more Smart Citations